Avaliação da contagem de linfócitos T, linfócitos B e células natural killer no estroma cervical de pacientes soropositivas e soronegativas para o HIV e com neoplasia intraepitelial cervical - Adriana Almeida de Souza Lucena (2011)
Assessment of T and B lymphocyte cell count and natural Killer cell count in the cervical stroma of HIV positive and negative women with cervical intraepithelial neoplasia. Objecives: To characterize the local immune response by measuring the expression of T lymphocytes (CD3+, CD4+, CD8+), B lymphocytes (CD20+) and Natural Killer cells (CD56+) in the cervical stroma of HIV positive and negative women with cervical intraepithelial neoplasia, investigating whether there are differences in the immune response among the groups and between groups ofhigh and low grade lesions. Patients and methods: This was a cross-sectional study which analyzed cone speciments by loop electrosurgical excision procedure in 85 patients, 47 of which were HIV-seropositive and 38 were HIV-seronegative. There were 46 cases of high grade CIN and 39 cases of low grade CIN. An immunohistochemical analysis of immunostained cells, located just below the CIN cells, was conducted. The microscopic reading of immunohistochemical analysiswas done by the most experienced observer in a subjective way. The results were grouped into high and low expression of immune cells. The statistical analysis used chi square test and Fishers exact test to compare categorical variables. The interactions among the variables were also investigated, based on odds ratio results. The multivariate analysis with logistic regression was performed, keeping the significant variables and interactions in the final model (p<0,05). In order to testfor goodness of fit for logistic regression, the Hosmer-Lemeshow test was used. Results: the univariate analysis comparing HIV status showed a significant decrease of TCD8+ lymphocytes in HIV-seronegative patients (p=0,03) as well as significant decrease of NK CD56+ cells in HIV-seropositive (p=0,01). There was no statistically significant difference in the expression of these cells in high and low grade CIN. The multivariate analysis showed that the variables CD8 (OR=0,34;IC95%=0,13-0,87) and CD56 (OR=4,48; IC 95%=1,23-16,3) were independently associated for HIV infection. In addition, variables CD3 x HIV (OR-4,79; IC95%=1,02-22,50) and CD20 x HIV (OR-0,12; IC95%=0,02-0,61) were independently associated for lesion grade. Conclusions: In general, there was a predominance of low expression of immune cells in both HIV-seronegative and HIV-seropositive petients and in high and low grade CIN. HIV infection was likely to have directly influenced the Natural Killer cell expression, showing a significantdecrease in HIV-seropositive patients. The pattern of TCD3 and TCD20lymphocyte expression in high and low grade CIN lesions, respectively, may have interacted with the presence of HIV.